2019
DOI: 10.1111/padm.12600
|View full text |Cite
|
Sign up to set email alerts
|

Navigating the dichotomy: The top public servant's craft

Abstract: How in their day‐to‐day practices do top public servants straddle the politics–administration dichotomy (PAD), which tells them to serve and yet influence their ministers at the same time? To examine this, we discuss how three informal ‘rules of the game’ govern day‐to‐day political–administrative interactions in the Dutch core executive: mutual respect, discretionary space, and reciprocal loyalty. Drawing from 31 hours of elite‐interviews with one particular (authoritative) top public servant, who served mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 34 publications
2
18
0
2
Order By: Relevance
“…Moreover, the compound image of agency governance is shown to be robust since no moderator variables are able to fundamentally change relationships from one governance type to another. The findings align with recent studies that have shown the compound roles of public agencies and their staff (e.g., Bach and Ruffing 2013; Egeberg 2006; Trondal 2011; van Dorp and Hart 2019). Correspondingly, the observations in this study challenge the alleged dyadic coordination dilemma facing agencies embedded in multilevel structures.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, the compound image of agency governance is shown to be robust since no moderator variables are able to fundamentally change relationships from one governance type to another. The findings align with recent studies that have shown the compound roles of public agencies and their staff (e.g., Bach and Ruffing 2013; Egeberg 2006; Trondal 2011; van Dorp and Hart 2019). Correspondingly, the observations in this study challenge the alleged dyadic coordination dilemma facing agencies embedded in multilevel structures.…”
Section: Discussionsupporting
confidence: 91%
“…De opvallende cross-tijd stabiliteit in de surveybevindingen roept de vraag op waarom de data geen trends weerspiegelen die zijn waargenomen in onderzoek dat over dezelfde periode van dertien jaar is uitgevoerd (Van den Berg, 2017;'t Hart & Kuijken, 2018;Van Dorp & 't Hart, 2019). Een mogelijke verklaring voor het ontbreken van reliëf in de gepercipieerde relevantie van politiek-strategisch inzicht is het feit dat de relevantie al als zeer hoog werd beschouwd aan het begin van de periode (4,66 of hoger op een vijfpuntsschaal).…”
Section: Conclusieunclassified
“…Understandings, of course, are resources civil servants work with. Understandings, in the most abstract sense, also encompass certain ends that an organization, occupation, or someone in a particular role tries to reach or contribute to (Schatzki, 2006; compare Paanakker, 2019; Van Dorp & ’t Hart, 2018).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Despite the growing interest in engagement, we know relatively little about the actual, everyday work of civil servants (Rhodes, 2016;Van Dorp & t Hart, 2018), particularly when it comes to a participatory context (Fenwick, 2012;Van Eijk et al 2019). To capture civil servants' work in public engagement, we started from a practice-theoretical approach (Cook & Wagenaar, 2012;Sandberg & Tsoukas, 2011;Wagenaar, 2004).…”
Section: Introductionmentioning
confidence: 99%